Mathematics in the Woods: Exploring Low-Income Parents’ Perceptions of and Involvement in Their Children’s Mathematical Learning - Lulu Sun (Northwest Journal of Teacher Education, 2022)
This article features data from a three-day mathematics camping trip that offered parents and their children time and space to enjoy non-digital activities and mathematics-building tasks. Drawing upon data from a larger qualitative study of children and their parents, this article specifically focuses on 10 parents’ perceptions of their children’s mathematics learning, problem-solving, and wellbeing. Findings suggest that, although parents are interested in their children’s mathematics learning, they are most concerned with their children’s development of problem-solving abilities and social skills. Moreover, students’ own learning experience is important for their mathematics learning.